History and activities of KU Leuven Laboratory of Acoustics - Glorieux Christ; Cops André; Vermeir Gerrit; Thoen Jan; Rychtáriková Monika (Acta Acustica)
The Laboratory of Acoustics at KU Leuven was founded more than 50 years ago. Until today, various acoustics-related topics, ranging from physical acoustics through building and room acoustics up to environmental acoustics and noise-related health issues, have been investigated. In the second half of the 20th century, the laboratory was one of the main centres of expertise in acoustics in Belgium, contributing to consulting and establishing legislation in building and environmental acoustics. In the 1990s, it also consolidated expertise in the characterisation of porous materials and was one of the driving research groups in the field of photoacoustics. During the past 15 years, additional research directions have been taken thanks to interdisciplinary collaborations, including psychoacoustics, perception of sound, sound quality assessment, archaeo-acoustics, tackling acoustic issues in building retrofit, and characterisation of walls materials in the framework of sustainable development (recycled materials, biomaterials etc.) This paper first brings a brief historical overview of the past activities of the Laboratory of Acoustics (and Thermal Physics) (ATF), its involvement in national and international collaborations and its main recent scientific and educational activities.